RELASI SUAMI ISTERI BERBASIS IḤSᾹN - Slamet Firdaus (Mahkamah : Jurnal Kajian Hukum Islam, 2017)
Abstrak Relasi suami isteri merupakan kebutuhan mendasar dalam mewujudkan kehidupan keluarga yang sakinah (usrah sakīnah). Kondisi ini menjadi manifestasi kedewasaan diri suami isteri menghadapi problematika krusial yang secara alamiah telah melekat pada keduanya, sekaligus menjadi faktor fundamental untuk menyelesaikannya akibat rasa cinta dan kasih sayang yang dianugerahkan Allah swt kepada keduanya. Namun keberadaan relasi tersebut tidak akan terealisasi dengan memadai dan sempurna, bila tidak didasari oleh iḥsān yang menekankan pada aspek spiritualitas yang menumbuhkan semangat dan kesadaran semata-mata ibadah (kehidupan adalah ibadah) kepada Allah swt, rasa takut (khashyah) karena pengawasan-Nya (murāqabah), dan menyuburkan kekuatan kehendak merasakan kehadiran-Nya dalam tatanan berkeluarga yang berakhlak karimah. Kata Kunci :Keluarga, Relasi, Ihsān, Sakīnah, akhlak karimah.     Abstract Marriage through teleconference communication media is one form of accommodation of public interest, this kind of marriage contract is an alternative effective and efficient choice (by not leaving Islamic sharia) for modern society. In the UUP 1974 and PP no. 9 of 1975 is stipulated only on the validity of marriages which are conducted on the basis of their religion and belief, namely as provided for in Article 2 paragraph (1) of the UUP 1974, further the marriage shall be registered at the Marriage Registration Office (Article 2 paragraph (2) of Jo. Paragraph (1) of Government Regulation No. 9 of 1975. Whereas in fiqh, the application of the terms and principles of marriage has a rational and transparent basis and reason to be implemented. Each determination should be followed by various reasons, Negative impact), as well as other things like the historical social setting that existed at that time. In connection with the marriage contract via teleconference, there are several points in the terms and pillars of marriage that must be analyzed which if applied can be a debate. Using normative approach, Marriage via teleconference both according to jurisprudence and positive law of Indonesia, can be studied the legal argument. If measured by the results Ijtihad of the previous scholars, especially the four mujtahid Imam, the marriage contract via teleconfrence can indeed be carried out under certain conditions and under certain circumstances. In this context means the marriage contract through teleconfrence can not be said to be legal, but it is casuistic in accordance with the situation at hand. Keywords; Akad Nikah, Teleconfrence, Majlis Akad, Witness and Recording